“Difference” as Mode of Resistance in Jane Austen’s Emma - Aziz ur Rehman (University of Chitral Journal of Linguistics and Literature, 2023)
This paper explores “difference” as locus for changing power relations in Jane Austen’s major novel Emma. While Austen’s pre-occupation with courtships has been under scholarly investigations, it has not been properly considered as tool of resistance: one that strives to displace power from physical force to a discursive one. This displacement is a strategic struggle of middle-class ascendency over aristocracy in a changing English milieu. The study examines courtships within two Foucauldian frameworks. The first one is disciplinary that aims to regulate sexual practices like panopticon---an apparatus of power, producing normative/heterosexual identity through surveillance. Embedded in the first is the second approach that examines the very assumptions of the panoptic discourse through ‘micro techniques of power’. It is the ability of her characters (especially the female) to reject not only undesirable sexual advances but desirable proposals as well that transform their otherwise passive and docile bodies into subjects to be reckoned with. In doing so, Austen does transform signs of class and rank into forms of expression as pre-requisite for any exchange. This paper is an attempt to look into the power dynamics in the novel from a different angle---the angle of difference impacted by power/knowledge and discourse. Two sites of contestation are analyzed: the first played between Emma Woodhouse and Mr. Knightly, and the second between Mrs. Elton and Jane Fairfax. This transformation can explicitly be viewed in her novel Emma. Foucauldian insights are certainly innovative to a well-read Austen.